Criterios de selección de imágenes en los archivos de televisión. - Caldera Serrano, Jorge (Revista General de Información y Documentación, 2000)
The selection of images in the state-owned telelvision companies is cha racterised by a series of factors alien to the information process itself since the primary selection of images will be imposed by the social reality and will ap pear as key event in the mass media. From the information science point of view, te selection process with which we are concerned is that made once the different images from news agencies, reporters, territorial centres, correspon dents, etc., have already entered the media.